2021
DOI: 10.3389/fphar.2020.622862
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Characterizing Serious Adverse Drug Reactions Associated With Drug-Drug Interactions in a Spontaneous Reporting Database

Abstract: Background: Drug-drug interactions (DDIs) are an important cause of adverse drug reactions (ADRs). In literature most of studies focus only on potential DDIs, while detailed data on serious ADRs associated with DDIs are limited. Our aim is to identify and characterize serious ADRs caused by DDIs using a spontaneous reporting database.Methods: All serious ADR reports, not related to vaccines and with a “definite”, “probable” or “possible” causality assessment, inserted into the National Pharmacovigilance databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
2
20
0
2
Order By: Relevance
“…In our study, 105 ADR reports were induced by actual DDIs, accounting for 18.32% of the ADR reports with more than one suspected drug. This percentage was close to the proportion reported by Magro et al (2020).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, 105 ADR reports were induced by actual DDIs, accounting for 18.32% of the ADR reports with more than one suspected drug. This percentage was close to the proportion reported by Magro et al (2020).…”
Section: Discussionsupporting
confidence: 89%
“…As DDIs are usually predictable and manageable, ADRs caused by DDIs may be prevented by monitoring the patient closely or replacing the responsible drugs with other medications. To reduce the risk of DDIs and improve patient safety, it is essential that healthcare professionals regularly review the medication regimens, recognize potentially interacting drug pairs, and withdraw unnecessary drugs (Magro et al, 2020). A prospective study showed that the number of patients with pDDIs and actual DDIs decreased by 18% and 43%, respectively, with an intervention based on a computerized Frontiers in Pharmacology frontiersin.org clinical decision support system containing information on drug combinations (Bertsche et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What is more, warfarin therapy is fraught with several inherent problems, such as great diversity in dosing, delayed onset of action along with prolonged effect after discontinuation, a wide range of serious interactions, and a narrow therapeutic index. Collectively, all these problems designate warfarin as a "high alert medication" that calls for extraordinary caution and care (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%